Pengaruh Capital Intensity, Inventory Intensity, dan Leverage terhadap Tax Avoidance - Norma Lutfita Sari; Ajimat, Ajimat (AKUA: Jurnal Akuntansi dan Keuangan, 2023)
This study aims to determine the effect of capital intensity, inventory intensity, and leverage on tax avoidance in LQ45 index companies for the 2017-2021 period. The type of research used in this research is associative quantitative. Data collection techniques use secondary data in the form of financial reports obtained from the Indonesia Stock Exchange (IDX) and the websites of each company. The method of analysis technique used in this study is descriptive analysis and uses multiple linear regression. The data that has been collected is processed with the help of E-views software version 10. The research was conducted on LQ45 index companies. The sample selection technique used purposive sampling, which was used as a sample of 17 companies with observations for 5 years 2017-2021 with a total sample data obtained of 85 sample data. The results of this study indicate that partially capital intensity has an effect on tax avoidance, while inventory intensity has no effect on tax avoidance, and leverage has no effect on tax avoidance. Simultaneously capital intensity, inventory intensity and leverage affect tax avoidance.